Military Expenditure and Economic Growth in Developing Countries: A Panel Data Analysis - Mohammed Khan, Twana Najaf (Al-Mashrof: Islamic Banking and Finance, 2025)
Over the past five decades, extensive empirical research has examined the defense–growth nexus, employing diverse methodologies, econometric techniques, and analytical frameworks, including case studies, cross-country analyses, and panel data studies. Despite this substantial body of work, the relationship between defense expenditure and economic growth remains inconclusive. Surprisingly, limited scholarly attention has been devoted to developing economies, even amid ongoing debates surrounding defense policy in these nations and its broader economic implications. This study addresses this gap in the literature by utilizing panel data methods to empirically assess the impact of defense spending on economic growth across 63 developing countries from 2015 to 2023. The findings, derived from robust panel estimation techniques, consistently indicate that military burden exerts a positive and statistically significant influence on economic growth in these contexts. Keywords: Military expenditure; Economic growth; Developing countries; and panel data methods